EVALUASI PENERAPAN AKUNTANSI PERSEDIAAN OBAT UNTUK PENENTUAN HARGA POKOK PENJUALAN PADA PT. CEMPAKA INDAH MURNI MANADO - Sandiri, Maissy P.; Ilat, Ventje; Pinatik, Sherly (JURNAL RISET AKUNTANSI GOING CONCERN, 2019)
Inventory is very important for the survival of the company, the company must be able to estimate the amount of inventory it supplies. This study aims to determine evaluation the application of drug inventory accounting for the determination of cost of goods sold at PT. Cempaka Indah Murni Manado which is engaged in the distribution of medicines. The application of drug inventory accounting conducted by PT. Cempaka Indah Murni Manado is suitable but the company does not recognize incoming transfers because the products sold at PT. Cempaka Indah Murni Manado was sent from the head office in Surabaya. The results of the research on the stock accounting report for inventory from January to December most of the items there are differences in selling price and incoming transfers every month. The analytical method used in this study is a qualitative descriptive method and conclusions are drawn from the recording its merchandise inventory is a computerized perpetual method, while for the method of determining the cost of inventory using the FIFO (First In First Out) method.Keywords: Inventory accounting, cost of goods sold